Privacy Management in Global Organisations - Pearson, Siani (Communications and Multimedia Security, 2012)
Meeting privacy requirements can be challenging for global organisations, particularly where future Internet service provision models are involved. In this paper approaches will be explained that can be used to help address these issues, with a focus on some of the solutions that the author has been involved in developing in HP Labs that are currently being used, rolled out or are the subjects of further research.